Erratum: The impact of precession on the observed population of ULXs (MNRAS (2023) 522 (5654) DOI: 10.1093/mnras/stab3049) - Khan, Norman; Middleton, Matthew J.; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2023)
This is a correction to the paper 'The impact of precession on the observed population of ULXs', published in MNRAS, 509 (2), 2493-2506 (2022). In our paper, we incorrectly reported the neutron star spin to have a value of a∗ = 0.01 when in fact we used a value of a∗ = 0.0005, in accordance with the known spin period of ULX pulsars (P = 1 s) and canonical values for the NS systems (M = 1.4 × 2 × 1033 g and I = 1045 g cm−2). This does not affect any results in the paper.
CRIS-Team Scopus Importer:2023-06-23